Study of Biogas Production Mechanism from Palm Oil Mill Effluent (POME) - Leong, Jing Yong (Penerbit Universiti Malaysia Perlis, 2011)
Palm oil mill effluent (POME) contains high chemical oxygen demand (COD) and biological oxygen demand (BOD) as it can pollutes the environment if it was directly discharge without prior treatment. Anaerobic digestion process that used in treat POME wastewater will released methane (CH4) gas and carbon dioxide (CO2) gas as final product which both gases are categories as greenhouse gases that will contribute to the Greenhouse Gases (GHG) Effect. Therefore, this study aims to examine COD removal efficiency of POME at closed anaerobic digestion, study on the production of methane gas at methanogenesis phase and also investigate on the amount of methane gas produce from each kilogram removal of COD. Operation of this study was proceed with the feed flow- rates of 375 mL/d, 450 mL/d, 560 mL/d, 750 mL/d and 1125 mL/d of raw POME wastewater which correspond to Hydraulic Retention Time (HRT)s of 12, 10, 8, 6, and 4 days. Duration for each feed flow-rate was 35, 18, 18, 15, and 20 days, respectively. The result indicated that the COD removal efficiency and the methane composition decreased from 66.09 mg/L to 47.30 mg/L and 48.50% to 19.27%, respectively as HRT decreased. As the decreased of methane composition, carbon dioxide composition was increased from 51.50% to 80.73% as reduce of HRT. While for VFA and ALK concentration, it shows an increment from 8622.86 mg CH3COOH/L to 12117.71 mg CH3COOH/L and 14280 mg CaCO3/L to 11544 mg CaCO3/L, respectively as the decreased of HRT. As the methane volume, it shows an increment from 532.06 mL CH4/day to 766.28 mL CH4/day as the decreased of HRT. These were attributed to variation of HRT that affects the system stability.